O perfil empreendedor em startups no modelo Born Global de internacionalização: uma abordagem qualitativa - Mesquita, Renato Furtado de (2017)
The Startups theme, companies with growth potential at scale through a repeatable and scalable business model, which has been widely discussed in the market, in the media and in scientific research. This theme shares a global vision that is also found in the concept of Born Globals (BGs), companies that, shortly after their emergence, become transnational corporations. This research is based on where these themes come together, the search for expansion to new markets of BGs and the scalability of Startups, with the perspective of understanding the Entrepreneur Profile (PE), which is a characteristic feature of those who move the economy, Of Startups with BGs features. In order to understand this profile, the characteristics defined by McClelland (1987), which are adopted by the United Nations (UN) and in Brazil widely disseminated by SEBRAE (Brazilian Service of Support to Micro and Small Companies) through the Empretec course . Thus, the present study le the present work raises the question: what is the profile of the entrepreneurs of Sstartups with Bborn Gglobal characteristics? To answer this question, we sought references in the literature on Entrepreneurship focused on Entrepreneur Profile, New Business focused on StartupStartups and Internationalization focused on Born GlobalBorn Globals. The study project is a qualitative research, composed of multiple case studies, where the unit of analysis are the entrepreneurs of Brazilian startups who have internationalized. Interviews were conducted to collect information through semi-structured scripts. The content analysis proposed by Bardin (2009) was used to obtain the research result, which pointed out an entrepreneurial profile that has a need of realization that evaluates the risks for the planning of the changes and does not worry so much about the power. Thus, the Startups Born Global Entrepreneur of international market as a single market and seeks to act fast to generate solutions in a lean way.